The Use of Board Games for EFL Learning: Teacher’s Perspective - Magfirotul Lailia; Pratnyawati Nuridi Suwarso; Iswahyuni Iswahyuni (Journey: Journal of English Language and Pedagogy, 2024)
Nowadays, digital-based media-integrated is needed in the learning context. This study aims to find out the teacher's perspective on the use of board games as a for EFL learning. This research used a descriptive qualitative approach with an in-depth interview instrument. The participant was one English teacher in a private Junior High School in Malang Regency. The data was displayed descriptively. With the advent of digital technology, the result showed that board game still have various benefits. By using board games, teacher motivate students and make the learning process understandable. Board games are also an effective teaching media for improving motivation in learning English. Board games increase student participation, motivation, and enjoyment, making learning more efficient and fun. It is showed that board games improve students' scores in English class. The board game showed that students were more active during English learning. It is concluded that board games improve students' ability to learn English. Thus, it is recommended that board games be used as a learning media for EFL learning.